Effect of Friction Stir Processing (FSP) to the Some Properties of Pure Copper Welded by Friction Stir Welding - Mais Abdulkareem (Engineering and Technology Journal, 2018)
Friction stir processing (FSP) is an innovative technique of varying the metallic features by intense, local plastic deforming. Accordingly, materials are stirred with no altering the phase via melting or otherwise to produce a microstructure with equiaxed and fine grains. This method enhances the microstructural features of metals. In This study the microstructure and the mechanical features including (tensile strength and microhardness), and radiographic inspection results are studied. All specimens of pure copper use in the (FSW) and (FSP) have variable rotating speed (900, 1200, and 1600 rpm) with constant feed speed (40 mm/min). The most remarkable results, the ultimate tensile strength for FSW and FSP at (1200 RPM and 40 mm/min) with the values of 250.4 MPa for FSW and 261..2 MPa for FSP and the efficiency reached 92.7% and 96.3% for FSP and FSW, respectively. The high hardness in the same sample was 118 HV for FSW and 135 HV for FSP. The microstructure at welding zones, specially nugget zone, is improved by the friction stir processing. Radiographic examination showed incomplete fusion of welding joint without defect.